2016
DOI: 10.18203/2349-2902.isj20163592
|View full text |Cite
|
Sign up to set email alerts
|

Split skin graft for diabetic ulcers: an analysis

Abstract: Background: Most diabetic wounds are slow healing and have a considerable area for which healing takes a long duration by conservative methods. Hence we wanted to check the effectiveness of methods of accelerating the healing process. Aim of the study was to analyse the effectiveness of split skin grafting as a curative procedure in these ulcers. Methods: A retrospective analysis of 100 cases of diabetic ulcer who had undergone split skin grafting between 2009 and 2012 was performed to check the effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Basic characteristics of the 11 studies are shown in Table 1. [12][13][14][16][17][18][19][20][21][22][23]…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Basic characteristics of the 11 studies are shown in Table 1. [12][13][14][16][17][18][19][20][21][22][23]…”
Section: Search Resultsmentioning
confidence: 99%
“…The weighted pooled recurrence rate was 4.2% (95% CI = 0.009-0.096, I 2 = 76%). 13 Hu et al 14 Jeon et al 16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation